2003
DOI: 10.1080/15287390306384
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Renal Effects in Children and Adults with Low Environmental Exposure to Heavy Metals

Abstract: The health effects of chronic exposure to heavy metals such as lead, cadmium, and mercury are widely documented, yet few data exist about the renal impact of low environmental exposure to these metals, particularly in children. The aim of this study was to assess renal parameters in children and adults living in an environment known for its past heavy metal contamination around two nonferrous smelters in northern France (Noyelles-Godault and Auby) and to compare their results with age and gender-matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 30 publications
6
34
1
Order By: Relevance
“…Smoking increased the internal exposure to cadmium and PAHs. The influence of breast feeding, gender and smoking were in agreement with other studies (Staessen et al, 2001;De Burbure et al, 2003;Strö mberg et al, 2003;Wilhelm et al, 2003;Wilhelm et al, 2006). Exposure to traffic, having exercised in the last three days and having a stove at home were associated with higher internal exposure to PAHs.…”
Section: Discussionsupporting
confidence: 92%
“…Smoking increased the internal exposure to cadmium and PAHs. The influence of breast feeding, gender and smoking were in agreement with other studies (Staessen et al, 2001;De Burbure et al, 2003;Strö mberg et al, 2003;Wilhelm et al, 2003;Wilhelm et al, 2006). Exposure to traffic, having exercised in the last three days and having a stove at home were associated with higher internal exposure to PAHs.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, none of the renal parameters studied showed any statistically significant differences between the 3 areas, either in girls or in boys (Tables 1 and 2) and no correlation was found between BCLs and the studied renal markers concentrations. This finding is in agreement with the results reported by de Burbure et al, conducted in French and Czech 8-12-yearolds with low BCLs (0.48 and 0.23 μg/l, respectively) [32,52], and it is also in agreement with the findings in Egyptian children with a relatively high cadmium level (1.34 μg/l) with no effects of this level on α-1-microglobulinuria, suggesting a subclinical renal effect after several years of cumulative exposure in children [59]. Moreover, Cikrt et al did not find any relationships between Cd-B and Alb-U or RBP-U in adults even with BCLs above 1 μg/l [74].…”
Section: Blood Cadmiumsupporting
confidence: 83%
“…In order to further analyze possible renal effects of lead exposure in children, we checked for any correlations between renal markers and BLLs within the smaller subgroups of children with high BLLs (above 50 μg/l, 70 μg/l and 100 μg/1), but no correlation was detected in these subgroups. This finding was in accordance with other studies describing renal biomarker anomalies in children at a low level of environmental exposure to lead [32,15]. Nevertheless, when we further analyzed the outcomes concerning BLLs effects on physical development of children, the only results found significant concerned girls from the urban area (N = 25) that had the highest BLLs mean in our population (89.451 μg/l) ( Table 1), and for whom BLLs were negatively correlated with height (r = -0.425, p = 0.034) and even negatively correlated with weight, but without clear significance (r = -0.369, p = 0.069).…”
Section: Blood Cadmiumsupporting
confidence: 83%
See 2 more Smart Citations